Jewish perspectives on Hellenistic rulers: [international colloquium in spring 2003 at the University of Southampton] - Rajak, Tessa (Hellenistic culture and society, 2007)
Philosophy and monarchy in the Hellenistic world / Oswyn Murray -- The character of Ptolemaic aristocracy: problems of definition and evidence / Jane Rowlandson -- Persia through the Jewish looking-glass / Erich Gruen -- Ben Sira on kings and kingship / Benjamin Wright -- The image of the Oriental monarch in the Third Book of Maccabees / Philip Alexander and Loveday Alexander -- The angry tyrant / Tessa Rajak -- The narrative function of the king and the library in the Letter of Aristeas / Sylvie Honigman -- Kingship and banditry: the Parthian empire and its western subjects / Richard Fowler -- Translating for Ptolemy: patriotism and politics in the Greek Pentateuch? / Sarah Pearce -- Poet and critic: royal ideology and the Greek translator of Proverbs / James Aitken -- The king's good servant?: Loyalty, subversion, and Greek Daniel / Jennifer Dines -- The terminology of government in the Septuagint--in comparison with Hebrew, Aramaic, and other languages / Lester Grabbe -- The court function of the interpreter in Genesis 42.23 and early Greek papyri / Trevor Evans -- The Greek Bible and Jewish concepts of royal priesthood and priestly monarchy / Arie van der Kooij -- Royal ideology: 1 and 2 Maccabees and Egypt / Jan Willem van Henten -- Constructing kings--from the Ptolemies to the Herodians: the archaeological evidence / Douglas Edwards